Updates in Anthracycline-Mediated Cardiotoxicity - Nebigil, Canan G.; Désaubry, Laurent (Frontiers in Pharmacology, 2018)
Cardiotoxicity is one of the main adverse effects of chemotherapy, affecting the completion of cancer therapies and the short- and long-term quality of life. Anthracyclines are currently used to treat many cancers, including the various forms of leukemia, lymphoma, melanoma, uterine breast, and gastric cancers. World Health Organization (WHO) registered anthracyclines in the list of essential medicines. However, anthracyclines display a major cardiotoxicity that can ultimately culminate in congestive heart failure. Taking into account the growing rate of cancer survivorship, the clinical significance of anthracycline cardiotoxicity is an emerging medical issue. In this review, we focus on the key progenitor cells and cardiac cells (cardiomyocytes, fibroblasts, and vascular cells), focusing on the signaling pathways involved in cellular damage, and the clinical biomarkers in anthracycline-mediated cardiotoxicity.